2021
DOI: 10.1101/2021.12.16.473009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards a global perspective for Salvia L: Phylogeny, diversification, and floral evolution

Abstract: Premise of this studySalvia is the most species-rich genus in Lamiaceae, encompassing approximately 1000 species distributed all over the world. We sought a new evolutionary perspective for Salvia by employing macroevolutionary analyses to address the tempo and mode of diversification. To study the association of floral traits with speciation and extinction, we modeled and explored the evolution of corolla length and the lever-mechanism pollination system across our Salvia phylogeny.MethodsWe reconstructed a m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 111 publications
0
3
0
Order By: Relevance
“…Our diversification analysis indicated no significant association between labellum shape and diversification ( Supplementary Table 5 ) with the CID4 model of HiSSE showing the smallest AIC value. On one hand the lack of association is somewhat surprising since other studies have shown a strong association with diversification and traits important for pollination such as with floral pigments ( Smith et al, 2010 ; Smith and Goldberg, 2015 ; Landis et al, 2018 ) and pollination trapping ( Xue et al, 2020 ), corolla length ( Moein et al, 2021 ), and corolla shape ( Fernandez-Mazuecos et al, 2013 ). However, other traits important for pollination appear to be decoupled with diversification such as the lever mechanism in Salvia ( Moein et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our diversification analysis indicated no significant association between labellum shape and diversification ( Supplementary Table 5 ) with the CID4 model of HiSSE showing the smallest AIC value. On one hand the lack of association is somewhat surprising since other studies have shown a strong association with diversification and traits important for pollination such as with floral pigments ( Smith et al, 2010 ; Smith and Goldberg, 2015 ; Landis et al, 2018 ) and pollination trapping ( Xue et al, 2020 ), corolla length ( Moein et al, 2021 ), and corolla shape ( Fernandez-Mazuecos et al, 2013 ). However, other traits important for pollination appear to be decoupled with diversification such as the lever mechanism in Salvia ( Moein et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…On one hand the lack of association is somewhat surprising since other studies have shown a strong association with diversification and traits important for pollination such as with floral pigments (Smith et al, 2010;Smith and Goldberg, 2015;Landis et al, 2018) and pollination trapping (Xue et al, 2020), corolla length (Moein et al, 2021), and corolla shape (Fernandez-Mazuecos et al, 2013). However, other traits important for pollination appear to be decoupled with diversification such as the lever mechanism in Salvia (Moein et al, 2021). Pollinator-mediated selection likely acts on more than one trait at a time to impact diversification, as observed by O'Meara et al (2016), who found that the presence of a corolla, bilateral symmetry, and reduced stamen number synergistically act as key innovations to double diversification rates.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation